Factors influencing the MSMEs’ decision to obtain halal certificate in Bogor district - Izzah, Hanifah Nurul; Irfany, Mohammad Iqbal (Halal Studies and Society, 2024)
According to Law No. 33 of 2014, the government requires halal certification for all food or drinks distributed in Indonesia, including those produced by Micro, Small and Medium Enterprises (MSMEs), the majority business owners. However, only 1 percent of MSMEs in Indonesia have halal certificates. Therefore, this study aimed to analyze the factors influencing the decision to have halal certificates by MSMEs in Bogor Regency using descriptive and multiple linear regression analysis. The primary data from 50 respondents interviewed using questionnaires were used. The results showed that branding positively influences the decision of MSMEs to have halal certificates. The halal awareness, regulations and certification facilities do not influence the decision to have halal certificatesSMEs to have a halal certificate.